Analysis of plane wave reflection and transmission phenomenon at the interface of two distinct micro-mechanically modeled rotating initially stressed piezomagnetic fiber-reinforced half-spaces. Issue 28 (16th December 2022) - Singh, A. K.; Mahto, S.; Guha, S.
Abstract: Analyzed the influence of normal/shear initial stresses and rotation on reflection/transmission characteristics of waves propagating at the interface of two distinct micro-mechanically modeled piezomagnetic fiber-reinforced composite(PMFRC) half-spaces composed of CoFe2 O4 fiber-epoxy matrix combination. An incident quasi-longitudinal(qP) wave generates reflected/transmitted quasi-longitudinal(qP), quasi-transverse(qSV), and magneto-acoustic(MA) waves, whose propagation directions are illustrated graphically. Transmitted qP wave has critical angles for considered initial stresses and rotation. Energy ratios of reflected/transmitted waves, interaction energy, and net energy are obtained, which satisfy the Law of Conservation of Energy, thereby validating this problem. Influences of incident angle, initial stresses, and rotation on amplitude/energy ratios are meticulously analyzed.